The British government and the city of London in the twentieth century - Michie, R. C. 1949-; Williamson, Philip 1953- (Cambridge University Press, 2004)
The relationship between the British government and the City of London has become central to debates on modern British economic, political and social life. For some the City's financial and commercial interests have exercised a dominant influence over government economic policy, creating a preoccupation with international markets and the strength of sterling which impaired domestic industrial and social well-being. Others have argued that government seriously constricted financial markets, jeopardising Britain's most successful economic sector. This 2004 collection of essays was the first book to address these issues over the entire twentieth century. It brings together leading financial and political historians to assess the government-City relationship from several directions and by examination of key episodes. As such, it will be indispensable not just for the study of modern British politics and finance, but also for assessment of the worldwide problem of tensions between national governments and international financial centres